Respons Benih Kakao Terhadap Amelioran, Mikrob Pelarut Fosfat, dan Pupuk Fosfat pada Tanah Masam - Kurnia Dewi Sasmita; Iswandi Anas; Syaiful Anwar; Sudirman Yahya; Gunawan Djajakirana (Jurnal Tanaman Industri dan Penyegar, 2020)
The growth of cacao in acid soils is commonly limited by some problems such as low available P and pH, and high Al saturation. Therefore, research is needed to solve the problem of coffee cultivation in acid soil. This study aimed to determine the effect of ameliorant, phosphate solubilizing microbes (PSM), and phosphate fertilizers (P) on the growth and nutrient uptake of cacao seedlings, and some acid soil properties. The study used a randomized block design with 3 factors and 3 replications. The first factor was ameliorant applications (without ameliorant, 10% organic fertilizer, 4% rice husk biochar, 4% rice husk biochar + 10% organic fertilizer). The second factor was PSM applications: without PSM, Burkholderia ambifaria (BPF) inoculants, and Aspergillus niger (FPF) inoculants. The third factor was P fertilizers applications (without Phosphate Rock (PR), 100, 200, and 400 mg P/kg of PR, and 400 mg P/kg of SP-36). The results showed that the applications of 4% rice husk biochar + 10% organic fertilizer + BPF or FPF inoculants increase the number of leaves by 77.9% and 69.2%, respectively, and increase the dry weight of shoot by 93.6 % and 101.9%, respectively. Phosphate rock application in media without organic fertilizer increases dry weight of shoots and roots of cacao seedlings, and the uptake of P, Ca, and Mg in shoots linearly in line with the increase of PR dose to 400 mg P/kg. Application of rice husk biochar significantly increased the acid phosphatase activity of growing media. Meanwhile, organic fertilizer increased the soil pH, acid phosphatase and available P activity, and decreased Al-dd growing media.